2020
DOI: 10.1097/der.0000000000000545
|View full text |Cite
|
Sign up to set email alerts
|

Contact Allergy to Fragrance Mix II and Hydroxyisohexyl 3-Cyclohexene Carboxaldehyde: A Retrospective Study by International Contact Dermatitis Research Group

Abstract: Background: Fragrance mix II (FM II) is included in the baseline patch test series recommended by the International Contact Dermatitis Research Group (ICDRG). Hydroxyisohexyl 3-cyclohexene carboxaldehyde (HICC) is the most important sensitizer of the 6 fragrance materials included in FM II. Besides being a part of FM II, HICC is also tested separately in the ICDRG baseline series.Objectives: The aim of the study was to investigate the prevalence of contact allergy to FM II and HICC in 2012-2016 with a focus on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 27 publications
5
8
0
Order By: Relevance
“…Interestingly, recent studies have proposed that patch testing with HICC might not be needed due to the overall low prevalence of positive reactions to HICC 5% pet. alone 23,24 . Our study found that 0.9% of the tested patients reacted to HICC without having a reaction to FM II; this result was three times the corresponding share reported by the ICDRG (0.3%) 23 .…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…Interestingly, recent studies have proposed that patch testing with HICC might not be needed due to the overall low prevalence of positive reactions to HICC 5% pet. alone 23,24 . Our study found that 0.9% of the tested patients reacted to HICC without having a reaction to FM II; this result was three times the corresponding share reported by the ICDRG (0.3%) 23 .…”
Section: Discussionsupporting
confidence: 53%
“…alone 23,24 . Our study found that 0.9% of the tested patients reacted to HICC without having a reaction to FM II; this result was three times the corresponding share reported by the ICDRG (0.3%) 23 . It might be that allergen exposure levels differ from one country to another, with HICC possibly being used more frequently in products in Thailand.…”
Section: Discussionsupporting
confidence: 42%
See 1 more Smart Citation
“…7 The gain by testing HICC as an individual allergen in addition to FMII has recently been questioned. 8 In general, an allergen is recommended to be included in the baseline series if at least 0.5% to 1.0% of suspected dermatitis patients react to the allergen. 9 The prevalence of HICC allergy exceeded 1% for the whole time period for both populations, although it decreased to 1% in the year 2019 in the Gentofte population.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are similar to those reported by others. 8 Hence, HICC does not fulfill the current criteria for inclusion in the European Baseline Series. For optimum performance in diagnosing fragrance contact allergy, routine application of the full set of 26 fragrances currently needing labeling is suggested.…”
Section: Discussionmentioning
confidence: 99%